Synthesis and Biological Evaluation of Novel 2-Substituted Analogues of (–)-Pentenomycin I - Zisopoulou, Stavroula A.; Bousis, Spyridon; Haupenthal, Jörg; Herrmann, Jennifer; Müller, Rolf; Hirsch, Anna K. H.; Komiotis, Dimitri; Gallos, John K.; Stathakis, Christos I. (Synlett, 2020)
A library of novel 2-substituted derivatives of the antibiotic natural product pentenomycin I is presented. The new collection of analogues is divided in two main classes, 2-alkynyl- and 2-aryl- derivatives, which are accessed by the appropriate type of palladium-catalyzed cross-coupling reaction of the 2-iodo-protected pentenomycin I with suitable nucleophiles. The new derivatives were tested for their activity against certain types of bacteria and one of them, compound 8h, was found to exhibit significant inhibitory activity against several Gram-positive bacteria but also displayed cytotoxic activity against eukaryotic cell lines.
Keywords: (–)-pentenomycin; Sonogashira; Suzuki; antimicrobial agents; Gram-positive bacteria